A Spatial Model of Effectiveness Criteria: Towards a Competing Values Approach to Organizational Analysis - Quinn, Robert E.; Rohrbaugh, John (Management Science, 1983)
This paper presents a framework for organizational analysis. The empirically derived approach does not emerge from the observation of actual organizations, but from the ordering, through multivariate techniques, of criteria that organizational theorists and researchers use to evaluate the performance of organizations. In a two-stage study, organizational theorists and researchers were impaneled to make judgments about the similarity of commonly used effectiveness criteria. The model derived from the second group closely replicated the first, and in convergence suggested that three value dimensions (control-flexibility, internal-external, and means-ends) underlie conceptualizations of organizational effectiveness. When these value dimensions are juxtaposed, a spatial model emerges. The model serves a number of important functions. It organizes the organizational effectiveness literature, indicates which concepts are most central to the construct of organizational effectiveness, makes clear the values in which the concepts are embedded, demonstrates that the effectiveness literature and the general literature on organizational analysis are analogues of one another, and provides an overarching framework to guide subsequent efforts at organizational assessment.